A comprehensive investigation of PRMT5 in the prognosis and ion channel features of lung cancer - Wang, Yan; Chu, Daifang; Li, Haichao; Fan, Jiangjiang; Zhu, Ximing; Ma, Yulong; Gu, Zhongping; Xie, Nianlin; Jing, Pengyu (Frontiers in Oncology, 2024)
The increasing incidence and mortality associated with lung cancer (LC) is a significant global health challenge. The underlying mechanisms contributing to LC remain inadequately understood. However, emerging evidence suggests that the epigenetic modifier protein arginine methyltransferase 5 (PRMT5) plays a complex role in various cellular processes, including DNA repair, gene transcription, and alternative splicing, through its function in catalyzing the symmetric dimethylation of both histone and non-histone proteins. In this study, we examined the functional role of PRMT5 utilizing LC-related datasets (GSE30219, GSE50081, and TCGA LC cohort) through a series of analyses. Our findings revealed that PRMT5 was significantly overexpressed in LC samples compared to normal tissues and was correlated with overall survival and disease-free survival rates. Additionally, PRDM1 was identified as a key protein exhibiting a strong interaction with PRMT5. The prognostic model that integrated PRMT5 with clinical factors demonstrated robust performance in assessing survival outcomes. Elevated levels of PRMT5 were associated with poor prognosis in LC, as evidenced by analyses of the GSE30219, GSE50081, and TCGA-LC datasets. Furthermore, we identified 27 ion channel (IC) genes exhibited a correlation with PRMT5 in lung adenocarcinoma (LUAD), of which 9 genes were identified as statistically significant with KM survival analysis. Strikingly, all of the 9 genes, including LRRC8A, the same as PRMT5, were associated with poor prognosis in LUAD. Our research highlights the potential of PRMT5 as a novel prognostic biomarker and its relationship with IC genes in LC.